Immature Gastric Teratoma in a Newborn: A Case Report - Sanjay Kumar; Hemant Yadav; Kamal Nain Rattan; Divya Srivastava; Abha Chandana; Sant Prakash (EL-Med-Pub, 2016)
A case of immature gastric teratoma in a neonate is being reported here. The neonate was presented with abdominal mass and distension and managed with excision of mass; the patient is doing fine postoperatively.